Anti-N-Methyl-D-Aspartate Receptor Encephalitis Associated With Clear Cell Renal Carcinoma: A Case Report - Yang, Jianhua; Li, Bin; Li, Xiaoquan; Lai, Zhaohui (Frontiers in Oncology, 2020)
Background: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a cause of autoimmune encephalitis and is characterized by epileptic seizures, psychosis, and consciousness impairments. It mostly affects young adults with ovarian cancers. We herein reported a case of anti-NMDAR encephalitis associated with clear cell renal carcinoma. Case Presentation: A 54-year-old male with headache for 1 week and mood and behavioral changes for 3 days was presented, but his clinical presentation and poor response to antiviral treatment did not support a diagnosis of viral encephalitis. Positive anti-NMDAR antibodies in serum and cerebrospinal fluid confirmed autoimmune encephalitis. A subsequent evaluation revealed a paraneoplastic etiology of a renal mass, and this was then resected and pathologically confirmed as clear cell renal carcinoma. The patient's symptoms showed improvement after resection of the mass. The patient relapsed 6 months after discharge, and the symptoms completely disappeared after treatment with corticosteroids and intravenous immunoglobulin. Conclusion: Our findings suggested that NMDAR encephalitis might be associated with clear cell renal carcinoma. When patients present with unexplained seizures, neuropsychiatric disorder, or other brain symptoms, clinicians should be careful with paraneoplastic neurological disorders. Early diagnosis and treatment of primary tumors might show improvement.